Synergistic Pressor Effect of Atomoxetine and Pyridostigmine in Patients With Neurogenic Orthostatic Hypotension. Issue 1 (January 2019) - Okamoto, Luis E.; Shibao, Cyndya A.; Gamboa, Alfredo; Diedrich, André; Raj, Satish R.; Black, Bonnie K.; Robertson, David; Biaggioni, Italo
Abstract : Patients with autonomic failure are characterized by disabling orthostatic hypotension because of impaired sympathetic activity, but even severely affected patients have residual sympathetic tone which can be harnessed for their treatment. For example, norepinephrine transporter blockade with atomoxetine raises blood pressure (BP) in autonomic failure patients by increasing synaptic norepinephrine concentrations; acetylcholinesterase inhibition with pyridostigmine increases BP by facilitating ganglionic cholinergic neurotransmission to increase sympathetic outflow. We tested the hypothesis that pyridostigmine will potentiate the pressor effect of atomoxetine and improve orthostatic tolerance and symptoms in patients with severe autonomic failure. Twelve patients received a single oral dose of either placebo, pyridostigmine 60 mg, atomoxetine 18 mg or the combination on separate days in a single blind, crossover study. BP was assessed seated and standing before and 1-hour postdrug. In these severely affected patients, neither pyridostigmine nor atomoxetine improved BP or orthostatic tolerance compared with placebo. The combination, however, significantly increased seated BP in a synergistic manner (133±9/80±4 versus 107±6/66±4 mm Hg for placebo, 105±5/67±3 mm Hg for atomoxetine, and 99±6/64±4 mm Hg for pyridostigmine; P <0.001); the maximal increase in seated BP with the combination was 33±8/18±3 mm Hg at 60 minutes postdrug. Only the combination showed a significant improvement of orthostatic tolerance and symptoms. In conclusion, the combination pyridostigmine and atomoxetine had a synergistic effect on seated BP which was associated with improvement in orthostatic tolerance and symptoms. This pharmacological approach could be useful in patients with severe autonomic failure but further safety and long-term efficacy studies are needed.